2015
DOI: 10.1021/acs.chemrestox.5b00174
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Studies of the Metabolic Activation of 8-Epidiosbulbin E Acetate

Abstract: Furanoid 8-epidiosbulbin E acetate (EEA) is a major constituent of herbal medicine Dioscorea bulbifera L. (DB), a traditional Chinese medicine herb. Our preliminary studies demonstrated that administration of EEA caused acute hepatotoxicity in mice, and the observed toxicity required cytochromes P450-mediated metabolism. Metabolic activation studies of EEA were performed in vitro and in vivo. Microsomal incubations of EEA supplemented with N-acetyl lysine (NAL) and glutathione (GSH) generated six metabolites (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 16 publications
1
48
0
Order By: Relevance
“…8-Epidiosbulbin E acetate (EEA) is another diterpenoid lactone isolated from DBL in 1984 (Murray et al, 1984). Unexpectedly, EEA is the most abundant diterpenoid in some DBL and its contents depend on the commercial source (Lin et al, 2015). Our previous studies found that the mice administered with EEA-containing DBL extracts showed 7.4-and 10.7-fold higher serum ALT and AST activities (ALT: 9128 ± 3487 U/L; AST: 7189 ± 4560 U/L) than those of the mice treated with EEA-free DBL extracts (ALT: 1093 ± 322 U/L; AST: 613 ± 194 U/L) (Lin et al, 2015).…”
Section: -Epidiosbulbin E Acetatementioning
confidence: 99%
See 2 more Smart Citations
“…8-Epidiosbulbin E acetate (EEA) is another diterpenoid lactone isolated from DBL in 1984 (Murray et al, 1984). Unexpectedly, EEA is the most abundant diterpenoid in some DBL and its contents depend on the commercial source (Lin et al, 2015). Our previous studies found that the mice administered with EEA-containing DBL extracts showed 7.4-and 10.7-fold higher serum ALT and AST activities (ALT: 9128 ± 3487 U/L; AST: 7189 ± 4560 U/L) than those of the mice treated with EEA-free DBL extracts (ALT: 1093 ± 322 U/L; AST: 613 ± 194 U/L) (Lin et al, 2015).…”
Section: -Epidiosbulbin E Acetatementioning
confidence: 99%
“…The furan moiety was proven to be metabolized to EEA-derived cis-enedial intermediate (EDE) in vitro and in vivo, which was subsequently trapped by GSH and/or NAL to offer six cyclic GSH/NAL conjugates (Scheme 10), and CYP3A4 was the dominant enzyme to catalyze the process (Lin et al, 2015). Serum ALT and AST levels of EEA-treated mice presented time-and dosedependent elevations.…”
Section: -Epidiosbulbin E Acetatementioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies also revealed that oral administration of ethanol extracts of D. bulbifera could cause the significant liver injury, together with increased lipid peroxide levels in liver ( Wang et al, 2010 ). Belonging to clane-type diterpene lactone with furane ring, diosbulbin B, diosbulbin D, and 8-epidiosbulbin E Acetate are principal constituents of D. bulbifera , which were verified to cause obvious liver toxicity towards on rat or mouse, respectively ( Lin et al, 2015 ; Lin et al, 2016a ; Lin et al, 2016b ). Although there is no furan in the structure of pulegone, it can be initially biotransformed to menthofuran after metabolism ( Thomassen et al, 1990 ), and menthofuran can further generate toxic metabolites, after metabolic activation ( Ravindranath et al, 1984 ; Ravindranath et al, 1986 ).…”
Section: Cyp450s Mediated Metabolic Activation Of Natural Products Leading To Toxicitymentioning
confidence: 99%
“… 18 The metabolic generation of six cyclic GSH/ N -acetyl lysine conjugates from EEA were detected both in vitro and in vivo . 19 To fully understand the hepatotoxicity effects and mechanism of the DLs, it is essential to obtain early information regarding its metabolism. However, compared with extensive researches on DIOB and EEA, the knowledge of the metabolites and metabolic pathways focusing on other DLs are limited.…”
Section: Introductionmentioning
confidence: 99%